CULTURAL TOURISM: STRATEGY TO IMPROVE THE QUALITY OF CULTUR-BASED TOURISM IN SLEMAN - Betsy, Elois Renata; Mistriani, Nina (ITB AAS Indonesia Surakarta, 2024)
Abstract Researchers believe that the Sleman area is a suitable area to apply the Cultural-Tourism concept in order to develop tourism in the Sleman area. Based on this, the researcher initiated this research. This research is a qualitative research with a descriptive approach which is related to Cultural Tourism, tourism in Sleman, and the application of the concept of Cultural Tourism in the city of Sleman. The data used in this research is secondary data that researchers obtained from various credible sources such as scientific articles, books and other sources commonly used in every research. These data were analyzed using the stages of data collection, data reduction, data selection, and drawing conclusions. The result in this article show 1. The Cultural-Tourism concept is a concept that does not only look at tourism development from profits, number of tourists, financial stability, physical development. However, this must go hand in hand with cultural values and historical values. 2. Tourism in the Sleman area is one of the regions in Indonesia that has the most physical cultural heritage in Indonesia compared to other regions. 3. The Cultural-Tourism concept is suitable to be applied in Sleman for 3 things, namely the abundance of physical cultural heritage, having a strong historical story, and being supported by a strong community character in protecting culture. Keywords: Cultural Tourism, Cultur-Based Tourism, Sleman